Sensor Array Design and Development of Smart Sensing System for Kick Force Visualization in Soccer. (2015) - Weizman, Yehuda; Fuss, Franz Konstantin
Abstract: Kicking performance in soccer is a major skill that can strongly influence the success of a team. A low-cost sensing platform was designed and developed to visualize the forces between a ball and smart sensing system. The instrumentation, consisting of piezoresistive material used as a novel pressure array and a programmable microcontroller, measures the magnitude of the kick force and centre of pressure (COP) with respect to a soccer boot coordinate system. The movement of the COP and the force vector diagram of curve kicks, colour-coded with progressing time, were displayed on a 4D model of a soccer boot in AutoCAD. The current study is a pilot to determine foot to ball impact characteristics which will ultimately be used for enhancement performance of kick accuracy in soccer.